HUBUNGAN LAMA BEKERJA, PENGAWASAN DAN KETERSEDIAAN FASILITAS SANITASI DENGAN PRAKTIK HIGIENE SANITASI PENJAMAH MAKANAN DI PT. BANDENG JUWANA ELRINA KOTA SEMARANG - Tesa Cahyaningsih; Nurjazuli Nurjazuli; Hanan Lanang Dangiran (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Food processing is a process of changing the selling value of a food becomes more useful. The ongoing processing will involve food handlers who will process the food until it becomes a clean and quality food product. Behavior of food handlers will affect the quality of products resulting from aspects of food hygiene and safety. The purpose of this study is to determine the relationship between the length of work, supervision and availability of facilities with the practice of food handlers. The type of this research is descriptive analytic with cross sectional approach. Number of population in this research is 169 workers production part of PT. Bandeng Juwana Elrina. The sample of this research is taken by purposive sampling and the sample size is 70 workers. Independent variables in this study include the length of work, supervision and availability of facilities while for the dependent variable in this study is the practice of food handlers. Data collection using questionnaires and observation sheets. Data analysis using Chi Square test to study the relationship between variables. The results showed that the long working variable (p value = 0,027) and the control variable (p value = 0,01) was related to the practice of applying sanitation hygiene by food handlers. While the facility availability variable (p value = 1,00) is not related to the practice of sanitation hygiene practices by food handlers. The conclusion of this research is that hygiene sanitation supervision and duration of work is a factor related to food handler practices and there is no relation between facility availability and hygiene practice of food handler so that in this case need to increase supervision and also do training for new employee so that the whole experience equal worker.